2015
DOI: 10.1002/hed.23961
|View full text |Cite
|
Sign up to set email alerts
|

Trends in chemoradiation use in elderly patients with head and neck cancer: Changing treatment patterns with cetuximab

Abstract: Background Cetuximab was approved for use in chemoradiation (CTRT) for locally-advanced head and neck squamous cell carcinoma (HNSCC) in 2006. Methods Among 3,705 patients with locally-advanced HNSCC identified in the linked Surveillance Epidemiology and End Results (SEER)-Medicare database, we assessed treatment trends including surgery, RT, CTRT and specific agents used in CTRT. We examined the influence of demographic and clinical characteristics on the likelihood of receiving CTRT before and after 2006. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 41 publications
(88 reference statements)
2
36
0
Order By: Relevance
“…More contemporary increases in CRT use are perhaps reflective of presumed improvements in supportive care, more conformal radiation techniques, or less toxic systemic therapies. In a recent analysis of the linked Surveillance, Epidemiology, and End Results (SEER)— Medicare database, Baxi et al (26) found that CRT use among head and neck cancer patients aged ≥65 years increased from 29% in 2001 to 61% in 2009. Furthermore, older age was associated with decreased likelihood of receiving CRT before 2006 but not afterward, which Baxi et al postulate is because of increased use of cetuximab in elderly patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More contemporary increases in CRT use are perhaps reflective of presumed improvements in supportive care, more conformal radiation techniques, or less toxic systemic therapies. In a recent analysis of the linked Surveillance, Epidemiology, and End Results (SEER)— Medicare database, Baxi et al (26) found that CRT use among head and neck cancer patients aged ≥65 years increased from 29% in 2001 to 61% in 2009. Furthermore, older age was associated with decreased likelihood of receiving CRT before 2006 but not afterward, which Baxi et al postulate is because of increased use of cetuximab in elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, older age was associated with decreased likelihood of receiving CRT before 2006 but not afterward, which Baxi et al postulate is because of increased use of cetuximab in elderly patients. Specifically, cetuximab was the most commonly used concurrent systemic agent among elderly patients after its Food and Drug Administration approval in 2006, and its rise coincided with the decline in use of platinum agents over the same period (26). Similarly, in our NCDB cohort, the rate of adjuvant CRT use among elderly patients (aged ≥70 years) with ECE or positive surgical margins increased from 13% in the period of 2004 to 2007 to 24% in 2008 to 2012, during which cetuximab was more commonly used.…”
Section: Discussionmentioning
confidence: 99%
“…55 This was predominantly driven by increased use of cetuximab, which accounted for approximately 50% of concomitant systemic therapy regimens in 2009. 58 However, the rising use of cetuximab in the older adult population should be scrutinized closely. As noted previously, the only trial showing a benefit with cetuximab in combination with RT demonstrated no improvement in survival in patients 65 or older.…”
Section: Methodsmentioning
confidence: 99%
“…The meta-analysis of Kim et al [12], which does not generally support the wide use of cetuximab concurrent to radiotherapy or CRT, highlights that cetuximab could be a reasonable and preferable choice in patients with comorbidities and a decreased performance status. All of these data have produced a substantial increase in chemotherapy and cetuximab plus radiation treatment in HNC as shown recently by the Surveillance Epidemiology and End Results (SEER) database [33]. After 2006, cetuximab became the most commonly used agent in concurrent regimens [33].…”
Section: Discussionmentioning
confidence: 99%
“…All of these data have produced a substantial increase in chemotherapy and cetuximab plus radiation treatment in HNC as shown recently by the Surveillance Epidemiology and End Results (SEER) database [33]. After 2006, cetuximab became the most commonly used agent in concurrent regimens [33]. …”
Section: Discussionmentioning
confidence: 99%